Medication Adherence of Patients with Renal Failure at Al-Diwaniyah Hospital - Haider Abd AL Ameer Twair (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Chronic kidney disease presents a profound global public health challenge, imposing severe therapeutic burdens on healthcare systems and affected individuals. Specific Background In clinical settings like the Fatima Al-Zahraa Dialysis Center at Al-Diwaniyah Teaching Hospital, managing renal failure requires complex lifelong pharmacological regimens to control comorbidities and slow down disease progression. Knowledge Gap Although clinical regimens are strictly prescribed, the specific socio-demographic drivers and patient-side behavioral factors influencing medication compliance in this particular regional cohort remain under-examined. Aims This study evaluates the overall medication adherence levels among patients experiencing renal failure and examines how their socio-demographic characteristics correlate with treatment compliance. Results Empirical analysis of 70 participants revealed that 58.6% exhibited low medication adherence, 31.4% showed moderate adherence, and only 10.0% maintained good adherence, with low awareness found in 72.9% of the sample. Statistical testing confirmed that while age, gender, occupation, and monthly income showed no significant correlation with compliance, a patient's level of education had a statistically significant association with their adherence behavior. Novelty This evidence identifies a direct correlation between formal literacy and compliance rates, shifting the analytical focus from generalized socio-economic barriers to targeted health literacy needs within the local hemodialysis population. Implications These findings demonstrate that standard clinical prescriptions are insufficient without proactive hospital education programs, highlighting the urgent need for structured nursing interventions and simplified drug regimens to minimize clinical relapses and reduce institutional mortality rates. Keywords: Medication Adherence, Renal Failure, Patient Compliance, Health Literacy, Hemodialysis Key Findings Highlights Low medication adherence was identified in more than half of the surveyed renal failure patients. Formal educational attainment has a significant statistical correlation with patient treatment compliance. Insufficient understanding of renal conditions directly drives non-adherence patterns in hemodialysis units.